Management of Credit Risk; the Case of South Akim Rural Bank Limited, Koforidua - Lartey, Odame Edward (2013)
A Thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters of Business Administration,